Abusive leadership and turnover intention: How employee and work engagement act as shields - Hadi, Syamsul; Sulistyawati, Eni; Kirana, Kusuma Chandra; Dianti, Cindy Alfianuri Imas; Purnasari, Eni; Ashakah, Felix Onoriode (Asian Management and Business Review, 2025)
Abusive behavior in organizations is widely acknowledged to increase employee turnover intention, but the exact nature of this relationship remains debated in academic circles. This study aims to validate a structural model integrating employee engagement and work engagement as mediators between abusive leadership and turnover intention, addressing a gap in the current literature. This study used Harry King Nomogram sampling techniques, and primary data was collected from 111 employees working in the digital company sector. Utilize surveys to collect data, and then use SmartPLS’s Confirmatory Factor Analysis and Structural Equation Modeling to evaluate research model hypotheses. The hypothesis test shows that abusive leadership negatively impacts employee engagement and work engagement, employee engagement negatively impacts turnover intention, and work engagement negatively impacts turnover intention. However, the positive impact of abusive leadership on turnover intention was not supported. The mediation analysis between abusive leadership and turnover intention, conducted through employee and work engagement, demonstrated a comprehensive mediation effect. Abusive leadership was not proven to positively affect turnover intention, which means that how abusive the leadership behavior is is not why employees increase internal turnover. However, turnover intention can be increased when employees are not involved personally or in work. Organizations must ensure that they always carry out work engagement and employee engagement as an alternative to retaining employees.